Contents of potentially toxic elements in sediments and waters of the Meža river and its tributaries draining mine waste deposits - Gosar, Mateja; Bavec, Špela; Miler, Miloš; Gaberšek, Martin (Geologija, 2024)
The results of the monitoring of the contents of potentially toxic elements (PTE) in sediments (2013, 2017, 2020) and waters (2017, 2020) of the Meža River and its tributaries, which drain mining waste deposits, are presented. A total of 13 sample sites were established in a sample scheme that enables long-term observation of the impact of mining waste deposits. In the sediments, the content of PTE, especially Pb, Zn, Cd, Mo and As, is greatly elevated and fluctuates with time. The study area is affected by more than 300 years of mining and ore processing industry. The differences in the contents in various years are most pronounced in the Meža River tributaries, which drain the mining waste dumps. Hydrological conditions have a significant influence on the contents in sediments, as PTE content increases with higher water level and higher water flow. Water erosion of mining waste dumps has a significant impact on the discharge of contaminated material into watercourses. In contrast, in the upper part of the Meža River, we did not observe strong influence of higher water level on the content of PTE in the sediments. Fluctuations in the content between individual years and fluctuations between various hydrological conditions are higher again in the middle part of the the Meža river, downstream from Žerjav. The presented results demonstrate that the contents of Pb, Zn, Cd, Mo and As in the sediments of the Meža River and its tributaries are very high and that they by far exceed the legislative critical value for the soil. PTE contents in the surface water are elevated in some locations and do not change significantly over time. The local concentrations of Pb, Cd and Zn exceed the legislative guidelines. We estimate that the dynamics of the sediment load in the Meža River along the towns of Črna na Koroškem, Žerjav and Mežica is very complex. In addition to mining waste deposits, the content of PTE in sediments and waters is also affected by scattered sources in the environment, such as contaminated soil and floodplains and their varying degrees of pollution, as the environment has been burdened by long-term mining, ore processing and smelting activities. Current industrial activity may also have an additional environmental impact.